Geeky f@b 5. #1, It's not rocket science - Lareau, Lucy; Lareau, Liz (Papercutz, 2018)
"Lucy Monroe's first day at Earhart Elementary is one for the yearbook: after meeting her new quirky 'pod' of girls in class, at recess, she has launched herself off the rusty monkey bars and splats face down on the blacktop. The principal closes the rickety playground, so now the whole school is mad! What's a new girl to do? Create a band of geeky friends to build a new play space together! The geeky f@b 5 is born! Meet animal lover Lucy; her sister and future Martian astronaut, Marina; math whiz and singer, Zara; robotics engineer, A.J.; computer coder and fashionista, Sofia; and Hubble, the snarky kitty. Can the gang convince classmates to build a new playground? Find out if the geeky f@b 5 can prove the meanies wrong, when they learn that when girls stick together, anything is possible!" -- Back cover of volume 1.